Geometric models for analyzing the shape of cauliflower heads - Anders, Andrzej; Jadwisieńczak, Krzysztof; Choszcz, Dariusz (Technical Sciences, 2024)
Selected geometric properties of cauliflower heads cv. Gohan F1 were analyzed by building numerical models with the use of a 3D scanner. Geometric models of cauliflower heads were developed in ScanStudio HD PRO, FreeCAD, and MeshLab programs. Five geometric models describing the shape of cauliflower heads were generated with the use basic geometric figures and drawing tools in FreeCAD. The geometry of numerical models and geometric models was compared in GOM Inspect. The surface area, volume, and detailed geometric dimensions of the developed models were determined. The deviations in cauliflower dimensions calculated by geometric models were mapped. The surface area, volume, and geometric dimensions of cauliflower heads were most accurately represented by the model generated with the Quadric Edge Collapse Decimation (QECD) function. In this model, the relative error of surface area measurements did not exceed 5%, and the relative error of volume measurements did not exceed 4%. This model was also characterized by the smallest average maximum deviation (+) and the smallest average minimum deviation (-) which was estimated at 8%. The proposed geometric model can be used for research and design purposes.